Kerja Luar Usahatani Oleh Rumahtangga Tani Padi di Kecamatan Tawangsari, Sukoharjo = Off-Farm Employment Of Rice Farm-Household In Kecamatan Tawangsari, Sukoharjo - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
Several studies emphasize the importance of off-farm income in the total family income. The purpose of this study is to know factors affecting off-farm work of rice farm-household in Kecamatan Tawangsari, Sukoharjo. The data used in this study were collected from sample farm-household. The sample in a stratified sampling based on farm size of more than 0,50 ha, 0,25-0,50 ha, and less than 0,25 ha. OLS multiple regression were used in analysis. The result suggested that off-farm wage had positive effect and farm size had negative effect on off-farm employment. For the larger farm size, off-farm work is affected by off-farm.wage positively. For the medium farm size, wage and number of household members had positive effect, while the distance had negative effect on off-farm work. Smaller farm size showed that wage and farm productivity had negative effect, while household income and number of adult members had positive effect on off-farm work.